2019
DOI: 10.3390/nano9081080
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Gold and Other Related Materials

Abstract: The field of nanomaterials continues to expand with the discovery of new nanostructures opening up new possibilities for both the study of unique physical properties and new applications [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Furthermore, the relationship between the material electron temperature and its porosity has also been demonstrated . As a result, NPG is the most extensively explored material owing to its chemical stability as well as optical, catalytic, and mechanical properties . Among several porous structures, the plasmonic properties of NPG films have been widely investigated ,,, intended for enhancements of SERS, , fluorescence emission, , and electrochemical and optical sensing .…”
Section: Preparation Strategies and Plasmonic Properties Of Nanoporou...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the relationship between the material electron temperature and its porosity has also been demonstrated . As a result, NPG is the most extensively explored material owing to its chemical stability as well as optical, catalytic, and mechanical properties . Among several porous structures, the plasmonic properties of NPG films have been widely investigated ,,, intended for enhancements of SERS, , fluorescence emission, , and electrochemical and optical sensing .…”
Section: Preparation Strategies and Plasmonic Properties Of Nanoporou...mentioning
confidence: 99%
“…76 As a result, NPG is the most extensively explored material owing to its chemical stability as well as optical, catalytic, and mechanical properties. 77 Among several porous structures, the plasmonic properties of NPG films have been widely investigated 7,8,78,79 intended for enhancements of SERS, 14,80 fluorescence emission, 13,81 and electrochemical and optical sensing. 3 Extensive reviews on NPGs and their application in plasmonic and other fields can be found in the literature.…”
Section: Preparation Strategies and Plasmonic Properties Of Nanoporou...mentioning
confidence: 99%
“…Recently, it has been shown that npAu can be used as a support for biomolecules in biosensors development studies, also as a catalyst for the oxidation of small molecules and as a material with plasmonic properties useful for optical sensing. This monolithic nanomaterial is known to exhibit a high surface area and so it can be easily functionalized with a thiol or disulfide groups in the context of self-assembled monolayers (SAMs) [21].…”
Section: Phthalocyanine-gold Nanoparticlesmentioning
confidence: 99%
“…Recently, it has been shown that npAu can be used as a support for biomolecules in biosensors development studies, also as a catalyst for the oxidation of small molecules and as a material with plasmonic properties useful for optical sensing. This monolithic nanomaterial is known to exhibit a high surface area and so it can be easily functionalized with a thiol or disulfide groups in the context of self-assembled monolayers (SAMs) [21]. In 2014, Wittstock and co-workers [22] reported the development of a npAu composite (npAu-ZnPc7) which demonstrated to have photocatalytic features; the synthesis was performed by coupling the Zn(II) complex of tetrakis(hex-5-ynyloxy)phthalocyanine (ZnPc7) with the nanoporous gold material functionalized with azide units (npAu-N3) (Scheme 7).…”
Section: Phthalocyanine-gold Nanoparticlesmentioning
confidence: 99%